Designing interface animation : meaningful motion for user experience - Head, Val, ....- (Brooklyn (N.Y.) : Rosenfeld Media, 2016)
Effective interface animation deftly combines form and function to improve feedback, aid in orientation, direct attention, show causality, and express your brand's personality. Designing Interface Animation shows you how to create web animation that balances purpose and style while blending seamlessly into the user's experience. This book is a crash course in motion design theory and practice for web designers, UX professionals, and front-end developers alike.
Keywords: Interfaces